2014
DOI: 10.3141/2432-01
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Surrogate Safety Assessment Model for Assessment of Intersection Safety

Abstract: The surrogate safety assessment model (SSAM) is a software application that reads trajectory files generated by microscopic simulation programs and calculates surrogate measures of safety. This approach eliminates the subjectivity associated with the conventional conflict analysis technique and allows assessment of the safety of a facility under a controlled environment before accidents occur. The specific goal of this research was to validate SSAM as a tool for accident prediction at urban intersections. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…The added value is also the study and results of the location of variable message signs in the VSL system on a road section developed using the SSAM. The SSAM has so far been used to assess road traffic safety mainly due to the geometric parameters of the road and fixed traffic organisation measures [ 29 ], parameters of intersections (signalised or unsignalised) [ 30 , 31 , 32 , 33 ] or ramp metering ITS services [ 34 ]. The location and the number of variable message signs along road sections, depending on the traffic volume or accompanying road incidents, can influence the places where dangerous spots occur.…”
Section: Introductionmentioning
confidence: 99%
“…The added value is also the study and results of the location of variable message signs in the VSL system on a road section developed using the SSAM. The SSAM has so far been used to assess road traffic safety mainly due to the geometric parameters of the road and fixed traffic organisation measures [ 29 ], parameters of intersections (signalised or unsignalised) [ 30 , 31 , 32 , 33 ] or ramp metering ITS services [ 34 ]. The location and the number of variable message signs along road sections, depending on the traffic volume or accompanying road incidents, can influence the places where dangerous spots occur.…”
Section: Introductionmentioning
confidence: 99%
“…Studies related to SSAM validation have been carried out by a number of researchers. For this reason, they compared the conflict data of SSAM simulation results with traffic accident data as well as traffic conflict data obtained from field observations [3,[11][12][13]. The result of the validity testing above is that the use of SSAM still has several limitations, but it is promising to be developed further in road safety measurement.…”
Section: Fig 7 Ssam Workflowmentioning
confidence: 99%
“…The results confirmed that the use of simulation models to evaluate road safety without proper calibration should be avoided, and more work is needed to confirm that simulated conflicts represent safety measures beyond what can be expected from exposure. Vasconcelos et al [16] evaluated the potential of the SSAM approach to assess the safety performance at urban intersections and roundabouts. Model validation was accomplished by comparing the number of conflicts obtained with the SSAM both with the number of crashes predicted by analytic models and with conflicts observed on existing intersections.…”
Section: Literature Reviewmentioning
confidence: 99%